2021
DOI: 10.5194/tc-15-3751-2021
|View full text |Cite
|
Sign up to set email alerts
|

What is the surface mass balance of Antarctica? An intercomparison of regional climate model estimates

Abstract: Abstract. We compare the performance of five different regional climate models (RCMs) (COSMO-CLM2, HIRHAM5, MAR3.10, MetUM, and RACMO2.3p2), forced by ERA-Interim reanalysis, in simulating the near-surface climate and surface mass balance (SMB) of Antarctica. All models simulate Antarctic climate well when compared with daily observed temperature and pressure, with nudged models matching daily observations slightly better than free-running models. The ensemble mean annual SMB over the Antarctic ice sheet (AIS)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
128
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 102 publications
(135 citation statements)
references
References 69 publications
7
128
0
Order By: Relevance
“…Furthermore, RCMs also improve the physical representations of specific processes over polar areas (Lenaerts et al, 2019). Mottram et al (2021) evaluated Antarctic SMB calculated from the outputs from five different RCM simulations driven by ERA-Interim (1987-2017. These five models showed mean annual SMB ranging from 1961 ± 70 to 2519 ± 118 Gt yr −1 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, RCMs also improve the physical representations of specific processes over polar areas (Lenaerts et al, 2019). Mottram et al (2021) evaluated Antarctic SMB calculated from the outputs from five different RCM simulations driven by ERA-Interim (1987-2017. These five models showed mean annual SMB ranging from 1961 ± 70 to 2519 ± 118 Gt yr −1 .…”
Section: Introductionmentioning
confidence: 99%
“…The overall model spread in SMB models corresponds to approximately 2 mm of sea level change per year. Mottram et al (2021) also showed that when compared to in situ observation from both automatic weather stations and glaciological stake measurements, the data availability proved insufficient to distinguish between better-performing model estimates. Fettweis et al (2020) found similar conclusions for Greenland, where the RCMs displayed different strengths and weaknesses when evaluated both spatially and temporally.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations